1956
DOI: 10.1037/h0043773
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cooperation and competition on the cohesiveness of small face-to-face groups.

Abstract: This is a study of the effects of cooperation and competition on group cohesiveness. The hypothesis was: "The cohesiveness of a small face-to-face group will increase under cooperative conditions and decrease under competitive conditions."The groups used were fourth grade children. The study revealed that the groups working under cooperative conditions in the experiment increased in cohesiveness, but that the groups that worked under conipetitive conditions did not necessarily decrease in cohesiveness. Of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

1965
1965
1997
1997

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…These studies have employed different group sizes, tasks, ages, and durations, yet the finding of greater interpersonal attraction in cooperative than in com petitive structures has persisted. Similar findings with respect to cohesiveness and attraction to group have been reported by Crombag (1966), Mizuhara and Tamai (1952), Phillips and DΆmico (1956), and Raven and Eachus (1963). Deutsch (1949a) showed groups in team competition to be more friendly and helpful than those in intragroup competition.…”
Section: Reward Structure and Social Connectednesssupporting
confidence: 77%
“…These studies have employed different group sizes, tasks, ages, and durations, yet the finding of greater interpersonal attraction in cooperative than in com petitive structures has persisted. Similar findings with respect to cohesiveness and attraction to group have been reported by Crombag (1966), Mizuhara and Tamai (1952), Phillips and DΆmico (1956), and Raven and Eachus (1963). Deutsch (1949a) showed groups in team competition to be more friendly and helpful than those in intragroup competition.…”
Section: Reward Structure and Social Connectednesssupporting
confidence: 77%
“…Because competition has been shown to decrease intrinsic motivation (Deci, BeHey, Kahle, Abrams, & Porac, 1981) and dampen creativity (Amabile, 1982a), competitive learning settings are interpreted as less intrinsically motivating and cooperative learning settings as more intrinsically motivating. A review of research by Johnson and Johnson (1974) corroborated that the cooperative setting promotes intrinsic motivation in trat it leads to less anxiety, greater task involvement, and a more positive emotional tone (all characteristics of intrinsically motivated behavior) than does competition (e.g., Haines & McKeachie, 1967;Phillips & D'Amico, 1956). Several studies have shown that problem solving tends to be more effective and achievement tends to be greater under cooperative than under competitive conditions (e.g., Laughlin & McGlynn, 1967;O'Connell, 1965;Wodarski, Hamblin, Buckholdt, & Ferritor, 1973).…”
Section: Intrinsically Motivated Learningmentioning
confidence: 96%
“…The results of the few studies available on the connections between competition and children's peer relations are indeed inconclusive. Phillips and D'Amico (1956) found that competition increased cohesiveness in some small groups of children, had the opposite effect in others, and had no effect in yet others. There is some suggestion that the degree of competition between friends depends on the situation, with more competitiveness found between friends in areas more relevant to the sense of personal identity (Tesser, Campbell, & Smith, 1984).…”
Section: Competition and Children's Peer Relationsmentioning
confidence: 94%